Surgical Intervention for Fetal Maceration in a 3.5 month Pregnant Crossbred Cow - Saini, Gitesh; Fernandes, Abhijeet; Kumar, Gaurav; Kumar, Dawoud Aamir Nehru; Bhardwaz, Anavil (The Indian Journal of Animal Reproduction, 2024)
This clinical article presents a case report detailing the successful surgical management of fetal maceration in a 3.5-month  pregnant crossbred cow using a left caudal paralumbar approach. Fetal maceration was diagnosed based on clinical  examination and ultrasound findings. A left caudal paralumbar approach was used under paravertebral anesthesia to  minimize disturbance to the surrounding structures and provide access to the uterus. The bony structure of macerated  fetus was gently removed. The cow exhibited a prompt recovery, with resumption of normal estrous cycles observed  within 65 days post-surgery.
Keywords: Fetal maceration; Cattle; Left flank approach